MANAJEMEN RISIKO ESTIMASI BIAYA PADA TAHAP PERENCANAAN PROYEK KONSTRUKSI - Yuliana, Ni Putu Indah; Ebtha Yuni, Ni Kadek Sri (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2024)
Cost estimation as a reference for analyzing the budget for the implementation of construction projects is very vulnerable to risks, so analysis is needed to reduce losses that can occur. The aim of study is to discover dominant risks, evaluate risks, define risk mitigation strategies and risks ownership to the cost estimation process at the planning stage. The research uses mix methods beetween qualitative and quantitative and data collection through surveys and interviews. The research respondents used the purposive sampling method. The results of the study showed that the identified risks amounted to 35 (thirty-five) risks and came from 9 (nine) risk sources. Risks that are included in the dominant category are unacceptable risks (unacceptable) as many as 10 risks and undesirable (undesirable) risks as many as 25 risks. The mitigation carried out is to appoint an experienced estimator, improve coordination between teams, ensure the availability and accuracy of data and learn more details of tender documents. The allocation of risk ownership on the contractor side is 33 risks (94.29%), followed by the owner and planning consultant each have 1 risk allocation (2.86%).